2007
DOI: 10.4141/cjps06023
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring corn and soybean agroecosystems after establishing no-tillage practices in Québec, Canada

Abstract: , H. 2007. Monitoring corn and soybean agroecosystems after establishing no-tillage practices in Québec, Canada. Can. J. Plant Sci. 87: 841-849. The conversion to no-tillage (NT) may seem risky to some producers who rely on tillage to control weeds, some insect pests and disease-causing pathogens that can reduce crop yield. Weeds, arthropods, and disease incidence were monitored in silage corn (Zea mays L.) and soybean (Glycine max L. Merr.) agroecosystems with CT and newly established NT plots in Ste-Anne-de-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In NT treatments, the greater P concentration in corn shoot indicates that P is not limiting corn growth, but something else is limiting. Under cool and humid climates as encountered in Quebec, enhancing soil drying and warming in spring are major advantages associated with MP (Whalen et al, 2007) that have contributed to better corn productivity in MP than NT systems. In addition, weeds and high surface residue cover favoring the proliferation of insect pests and pathogens could negatively impact corn growth in the NT plots (Burgess et al, 1996; Mehdi et al, 1999; Whalen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In NT treatments, the greater P concentration in corn shoot indicates that P is not limiting corn growth, but something else is limiting. Under cool and humid climates as encountered in Quebec, enhancing soil drying and warming in spring are major advantages associated with MP (Whalen et al, 2007) that have contributed to better corn productivity in MP than NT systems. In addition, weeds and high surface residue cover favoring the proliferation of insect pests and pathogens could negatively impact corn growth in the NT plots (Burgess et al, 1996; Mehdi et al, 1999; Whalen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Under cool and humid climates as encountered in Quebec, enhancing soil drying and warming in spring are major advantages associated with MP (Whalen et al, 2007) that have contributed to better corn productivity in MP than NT systems. In addition, weeds and high surface residue cover favoring the proliferation of insect pests and pathogens could negatively impact corn growth in the NT plots (Burgess et al, 1996; Mehdi et al, 1999; Whalen et al, 2007). Thus, under NT, the beneficial effects of the greater corn P concentration on shoot biomass production seem to be compromised by other limitations controlling the growth of plants, particularly under cool and humid climates.…”
Section: Discussionmentioning
confidence: 99%
“…In the same test they determined that there was no significant influence of tillage practice on soybean yield with NT yielding 6% more than CT on average, and that following five years of continuous corn, soybean yield increased by 8% over continuous soybean. In a five year study of a silage corn soybean rotation in Quebec, Whalen et al (2007) found that CT silage corn was significantly higher yielding than NT silage corn in three of five years and had similar yields in the other two years. They also determined that CT soybean had greater yield than NT soybean in two of five years and similar yield in three of five years and proposed that corn yields were reduced under NT due to root constraints rather than weed competition or insect or disease damage.…”
mentioning
confidence: 98%
“…Tillage typically decreases the abundance or activity density of soil macro arthropods such as ground beetles and spiders (Araneae, House and Parlee, 1985, Stinner and House, 1990, Holland and Reynolds, 2003, Thorbek and Bilde, 2004 Baraibar et al, 2009, Errouissi et al, 2011. However, some studies show either no effect of tillage (Carcamo et al, 1995, Baguette and Hance, 1997, Huusel-Veistola, 1998, or a positive effect of tillage (Carcamo 1995, Whalen et al, 2007, and results often vary by taxon (Tonhasca, 1993, Baguette and Hance, 1997, Shearin et al, 2007, Thorbeck and Bilde, 2004. Results for pests and invertebrates living in foliage are even more variable (Stinner et al, 1988, Stinner and House, 1990, Tonhasca, 1993, Costamagn and Landis, 2006, Whalen et al, 2007, Hatten et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies show either no effect of tillage (Carcamo et al, 1995, Baguette and Hance, 1997, Huusel-Veistola, 1998, or a positive effect of tillage (Carcamo 1995, Whalen et al, 2007, and results often vary by taxon (Tonhasca, 1993, Baguette and Hance, 1997, Shearin et al, 2007, Thorbeck and Bilde, 2004. Results for pests and invertebrates living in foliage are even more variable (Stinner et al, 1988, Stinner and House, 1990, Tonhasca, 1993, Costamagn and Landis, 2006, Whalen et al, 2007, Hatten et al, 2010. The negative effect of increased tillage on at least some invertebrate taxa might explain some of the variability in invertebrate response to organic field management.…”
Section: Introductionmentioning
confidence: 99%